Some factors of fibrogenesis and angiogenesis as biomarkers of renal scarring in children with vesicoureteral reflux - Макєєва, Н.І.; Морозова, О.О.; Ярова, К.К.; Сергієнко, К.В.; Макаренко, Р. (ХНМУ, 2020)
Introduction and Aim. One of the most common forms of congenital obstructive uropathy in children is vesicoureteral reflux (VUR), which is observed in 1-2% of pediatric population, and its incidence in urinary tract infection is 70%. According to the International Committee for the Study of Reflux, the incidence of nephrosclerosis in VUR among children of the European population is 48% and it results in the development of the terminal stage of chronic renal failure in 25-60% of patients. Approximately 25% of children with renal scarring (RS) resulting from VUR require hemodialysis and kidney transplantation. The aim of the study was to improve the early diagnosis of the formation and progression RS in children with VUR and chronic pyelonephritis by assessing the urine levels of transforming growth factor beta1 (TGF-β1) and vascular endothelial growth factor (VEGF).
Keywords: vascular endothelial growth factor; renal scarring